ANALYSIS OF WORKLOAD AND LABOR NEEDS USING THE WORKLOAD INDICATOR STAFFING NEED (WISN) METHOD TO INCREASE EMPLOYEE PERFORMANCE EFFICIENCY IN HOSPITALS AISYIYAH SITI FATIMAH TULANGAN - Efendi, Dia Nita; Putri, Mia Nasrida; Kobo, Stephanie Yuli Ranti; Sumartik , Sumartik (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The aim of this research is to determine the description of labor requirements, workload in each hospital unit, and measure the appropriate workload balance to produce efficient performance based on the WISN (Workload Indicator Staffing Need) method at Aisyiyah Siti Fatimah Tulangan Hospital. Method: The research design uses quantitative descriptions with work sampling and observation techniques in data collection. The population in this study was all units working at the hospital, and the sample used a different calculation method of 15 units. Results: The research results show that the available working time is 270.1 hours per year or the equivalent of 113,460 minutes per year with a standard allowance of 0.1786, equivalent to 18%, which is in accordance with general workload standards. From the results of this research, there is a gap between the workload calculation methods for each unit. The Pharmacy Unit, Laboratory Unit, and Registration Administration Unit do not use the WISN method for workforce planning. So the calculation results show an excess workload which causes a lack of labor requirements. Novelty: It was concluded that Aisyiyah Siti Fatimah Tulangan Hospital requires alignment of workload calculations with the WISN method to plan workforce productivity efficiency with a focus on main tasks and functions.